DETERMINAN TINGKAT EFISIENSI BANK PEMBANGUNAN DAERAH (BPD) SYARIAH DI INDONESIA: TWO-STAGE DATA ENVELOPMENT ANALYSIS - Hilda Sukma Puspita; Atina Shofawati (Universitas Airlangga, 2018)
This study aims to analyze the efficiency level of Sharia Regional Development Bank on the first stage and to analyze the influence of Bank Size, ROA, NPF, FDR and Inflation for the efficiency level of Sharia Regional Development Bank on the second stage. The population in this study is the Sharia Regional Development Bank in Indonesia. The sample used in this research is 14 Shariah Regional Development Bank that fulfill the criteria of taking the sample that is having Sharia Business Unit, presenting the financial statements and has been published, and no change of business entity. The observation period of the study is from 2012 to 2016. This researchanalysis technique used DEAP 2.1. on the one stage and Tobit on the twostage. The result of this study indicates that the Bank Size, ROA and FDR positif significant influence to efficiency level, while the NPF and Inflation don’t have influence to efficiency level. REFERENCESAbidin, Zaenal dan Endri. 2009. Kinerja Efisiensi Teknis Bank Pembangunan Daerah: Pendekatan Data Envelopment Analysis (DEA). Jurnal Akuntansi dan Keuangan, Vol. 11, No.1, pp.21-29.Al-Quran dan Terjemahan.2014. Kementrian Agama RI dengan Transliterasi Arab-Latin.Basyaib, Fachmi. 2007. Keuangan Perusahaan. Edisis Pertama. Jakarta: Kencana Prenada Media Group.Begum, Nur Sabrina.2015. Analisis Tingkat Efisiensi Perbankan Syariah Di Indonesia Tahun 2010-2014 Dengan Menggunakan Metode Data Envelopment Analysis.Skripsi tidak diterbitkan. Universitas Airlangga.Berger, A.N dan Mester, L, J. 1997. Inside The Black Box: What Explains Differences In The Efficiency of Financial Institusions. Journal of Banking and Finance, 21, 895-947.Fadhlullah, Ahmad H. 2015. Efisiensi Bank Pembangunan Daerah: Pendekatan Stochastic Frontier. Signifikan, Vol. 4, No.1, April 2015.Fathony, Moch. 2012. Estimasi Dan Faktor-Faktor Yang Mempengaruhi Efisiensi Bank Domestik Dan Asing Di Indonesia. Jurnal Keuangan dan Perbankan, Vol.16, No.2, Mei 2012, hlm.223-237.Firdaus, Muhammad F. dan Muhamad Nadratuzzaman H. 2013.Efisiensi Bank Umum Syariah Menggunakan Pendekatan Two-Stage Data Envelopment Analysis.Buletin Ekonomi dan Perbankan, Vol. 16, No. 2, Oktober 2013.Gujarati, Damodar. 2003. Basic Econometrics. Fourth Edition. Boston: McGraw-Hill.Hadad, M. Santoso, W. Dhaniel, I. Mardhanugraha, E. 2003. Analisis Efisiensi Industri Perbankan Indonesia: Penggunaan Metode Non-Parametrik Data Envelopment Analysis (DEA). Research Paper Bank Indonesia, No.7/5.Ismail, Farhana, Rossazana Ab. Rahim, dan M. Shabri Abd. Majid. 2012. Determinant of Efficiency in Malaysia Banking Sector. International Procedings of Economics Development and Research, Vol. 43, pp.238.Kamaruddin, dkk.2008. Asseing Production Efficiency of Islamic Banks and Conventional Bank Islamic Windows in Malaysia.International Journal of Business and Management Science, Vol 1(1), hlm.31-48.Mankiw, N. Gregory. 2004. Pengantar Ekonomi Makro. Edisi Ketiga. Jakarta: Salemba Empat.Mishkin, Frederic S. 2010. Ekonomi Uang, Perbankan dan Pasar-Pasar Keuangan. Jakarta: Salemba Empat.Muharam, Harjum dan Rizki Pusvitasari. 2007. Analisa Perbandingan Efisiensi Bank Syariah di Indonesia dengan Metode Data Envelopment Analysis Periode Tahun 2005. Jurnal Fakultas Ekonomi Universitas Diponegoro, Vol.11, No. 03, Desember 2007.Noor, M.A.N.M dan Hayati, N.A. 2011. The Determinants of Islamic Bank’s Efficiency and the Impact of the 1998 and 2008 Financial Crises. Review of Islamic Economics, Vol. 15, No. 1, pp.37-69.Pambuko, Zulfikar Bagus. 2016. Determinan Tingkat Efisiensi Perbankan Syariah Di Indonesia: Two Stages Data Envelopment Analysis. CAKRAWALA, Vol. XI, No. 2, Desember 2016.Permono, Iswardono S. dan Darmawan.2000. Analisis Efisiensi Industri Perbankan Di Indonesia (Studi Kasus Bank-Bank Devisa Di Indonesia Tahun 1991-1996).Jurnal Ekonomi Dan Bisnis Indonesia, XV(1).Pratikno, Heri dan Iis Sugianto. 2011. Kinerja Efisiensi Bank Syariah Sebelum dan Sesudah Krisis Global Berdasarkan Data Envelopment Analysis. Jurnal Ekonomi Bisnis, Vol.16(2), pp.108-117.Rabbani, Farhan. 2014. Analisis Perbandingan Efisiensi Bank Pembangunan Daerah dan Unit Usaha Syariah BPD Sebelum dan Sesudah Penerapan BPD Regional Champion (BRC) dengan Metode Data Envelopment Analysis (DEA). Skripsi tidak diterbitkan. Universitas Syarif Hidayatullah.Ramly, Ar Royyan. 2015. Tingkat Efisiensi Bank Pembangunan Daerah (BPD) Di Indonesia Periode 2012-2014. Disertasi tidak diterbitkan. Universitas Serambi Mekkah.Siamat, Dahlan. 2001. Manajemen Lembaga Keuangan. Edisi Ketiga. Jakarta: Badan Penerbit Fakultas Ekonomi Universitas Indonesia.Sufian, Fadzlan dan Noor M.A.N.M. 2009. The Determinants of Islamic Bank’s Efficiency Changes Empirical Evidence from the MENA and Asian Banking Sectors. International Journal of Islamic and Middle Eastren Finance and Management, Vol. 23, No. 3.Sufian, Fadzlan dan Muzafar Shah Habibullah. 2010. Development in the Efficiency of the Thailand Banking Sector: a DEA Approach. International Journal of Development Issues, Vol. 9, No. 3, pp 226-245.Sugiyono. 2003. Metode Penelitian Bisnis. Bandung: Pusat Bahasa Departemen Pendidikan Nasional.Undang-Undang Republik Indonesia. 1962. Undang-Undang Republik Indonesia Nomor 13 Tahun 1962 Tentang Ketentuan-Ketentuan Pokok Bank Pembangunan Daerah.Weston, J. Fred dan Thomas E. Copeland. 1998. Manajemen Keuangan. Edisi 8. Jakarta: Bina Rupa Aksara.Wheelock, D.C dan P. Wilson. 1999. Technical Progress Inefficiency and Productivity Change in US Banking. Journal of Money, Credit and Banking, Vol. 31, pp 212-234.Yudistira, D. 2004. Efficiency in Islamic Banking: An Empirical Analysis of Eighteen Banks. Islamic Economic Studies, 12(1).